Damping off on soybean (Glycine max) caused by Pythium aphanidermatum in Buenos Aires Province (Argentina) - Grijalba, Pablo Enrique (2020)
Pythium aphanidermatum has a cosmopolitan distribution in the warmer parts of the world. The aim of this study was to identify the causal agent of damping off in soybean seedlings on late planting dates under hot conditions, from different locations in Buenos Aires province. The isolates induced different levels of plant and seedling death and growth rate at different incubation temperatures (15, 25 and 35°C). In accordance with morphological, cultural and molecular characteristics, the pathogen was identified as P. aphanidermatum, and this is the first report of this oomycete causing soybean root and stem rot in Buenos Aires province, Argentina.